Concerted Gene Expression of Hippocampal Steroid Receptors during Spatial Learning in Male Wistar Rats: A Correlation Analysis - Lubec, Gert; Korz, Volker (Frontiers in Behavioral Neuroscience, 2016)
Adrenal and gonadal steroid receptor activities are significantly involved and interact in the regulation of learning, memory and stress. Thus, a coordinated expression of steroid receptor genes during a learning task can be expected. Although coexpression of steroid receptors in response to behavioral tasks has been reported the correlative connection is unclear. According to the inverted U-shape model of the impact of stress upon learning and memory we hypothesized that glucocorticoid receptor expression should be correlated to corticosterone levels in a linear or higher order manner. Other cognition modulating steroid receptors like estrogen receptors should be correlated to glucocorticoid receptors in a quadratic manner, which describes a parabola and thus a U-shaped connection. Therefore, we performed a correlational meta-analyis of data of a previous study (Meyer and Korz, 2013a) of steroid receptor gene expressions during spatial learning, which provides a sufficient data basis in order to perform such correlational connections. In that study male rats of different ages were trained in a spatial holeboard or remained untrained and the hippocampal gene expression of different steroid receptors as well as serum corticosterone levels were measured. Expressions of mineralocorticoid (MR) and glucocorticoid (GR) receptors were positively and linearly correlated with blood serum corticosterone levels in spatially trained but not in untrained animals. Training induced a cubic (best fit) relationship between mRNA levels of estrogen receptor α (ERα) and androgen receptor (AR) with MR mRNA. GR gene expression was linearly correlated with MR expression under both conditions. ERα m RNA levels were negatively and linearily and MR and GR gene expressions were cubicely correlated with reference memory errors (RME). Due to only three age classes correlations with age could not be performed. The findings support the U-shape theory of steroid receptor interaction, however the cubic fit suggest a more complex situation, which mechanisms may be revealed in further studies.